IMPACT OF CRUCIFER PLANT EXTRACTS ON AFLATOXIN B1-TREATED MAIZE SEEDS ON SEEDLING GROWTH - Kumar, Mahesh; Prasad, Gajendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This investigation assesses the phytotoxic effects of aflatoxin B1 on maize (Zea mays L.) seedling shoot and root growth and examines the protective potential of three crucifer plant extracts. Maize seeds treated with aflatoxin B1 exhibited significant reductions in shoot length (up to 76.47%) and root length (68.42%) at the highest concentration tested. Co-application of crucifer extracts markedly alleviated these effects, with extract C demonstrating the greatest efficacy, reducing shoot length inhibition to 44.12% and root length inhibition to 36.84%. Extracts alone slightly enhanced shoot and root lengths compared to untreated controls, suggesting a dual role as growth promoters and stress mitigators. These findings highlight the potential of crucifer extracts, particularly C, as natural interventions to enhance maize seedling resilience against aflatoxin B1 stress, offering a promising strategy for sustainable agriculture in contamination-prone regions like Bihar, India.